The influences of LaVO4:Eu3+,Cr3+ red phosphors on white light-emitting diode applications - Nguyen Hung Khanh; Nguyen Le Thai; Thuc Minh Bui; Huu Phuc Dang; Huynh Thanh Thien (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
In this present paper, the LaVO4:Eu3+,Cr3+ (LV:Eu,Cr) red-orange phosphorsare introduced in WLED fabrication. The LV:Eu,Cr phosphor is synthesized with high-temperature solid-phase reaction. The luminescence properties of the phosphor are monitored with ultraviolet-visible and near-infrared (UV-vis-NIR) measurements. The heat generating in the phosphor sample is also investigated with different power densities of the 980 nm laser. The phosphor exhibits absorption bands at 254 nm and 316 nm, suitable for UV light-emitting diodes (UV LED) applications. The Cr3+ concentrations have noticeable effects on the luminescence of the phosphor. The increasing Cr3+ dosage initiates reduction in Eu3+ emission intensity and luminescence lifetime average. The heat-activated amount in the phosphor is also significant with the higher concentration of Cr3+ ions. When using the LV:Eu,Cr phosphor in white light-emitting model (WLED), the dominant red-orange emission centered at 595 nm is observed, in addition to the blue peak at 453 nm. The luminosity, color rendition, and color uniformity of the WLED light are also discussed. The findings indicate that the phosphor can be combined with other high-efficiency blue and green phosphors to obtain the improved color rendition and luminous performances and used in heat-creating optical applications.